The tandem repeat modules of Xist lncRNA: a swiss army knife for the control of X-chromosome inactivation. (17th December 2021) - Raposo, Ana Cláudia; Casanova, Miguel; Gendrel, Anne-Valerie; da Rocha, Simão Teixeira
Abstract : X-inactive-specific transcript ( Xist ) is a long non-coding RNA (lncRNA) essential for X-chromosome inactivation (XCI) in female placental mammals. Thirty years after its discovery, it is still puzzling how this lncRNA triggers major structural and transcriptional changes leading to the stable silencing of an entire chromosome. Recently, a series of studies in mouse cells have uncovered domains of functional specialization within Xist mapping to conserved tandem repeat regions, known as Repeats A-to-F. These functional domains interact with various RNA binding proteins (RBPs) and fold into distinct RNA structures to execute specific tasks in a synergistic and coordinated manner during the inactivation process. This modular organization of Xist is mostly conserved in humans, but recent data point towards differences regarding functional specialization of the tandem repeats between the two species. In this review, we summarize the recent progress on understanding the role of Xist repetitive blocks and their involvement in the molecular mechanisms underlying XCI. We also discuss these findings in the light of the similarities and differences between mouse and human Xist .